Enabling strategies that influence on educational and occupational choices of visually impaired adolescents - Castignani, María Laura (2017)
In this work we present some of the results of the doctoral thesis: “Guidance and visual impairment. Factors that influence the adolescent choices, linked with the investigation: “Evaluation of inclusion strategies to reduce university dropout and reorientation in other educational-training areas”.** (Gavilán, 2014-2017 cód. S035). In this regard we investigated factors that guide the educational and occupational choices of adolescents and young people with visual impairment: blind people, deeply and mild visually impaired, who were completing high school. It is a part of the Theoretical Operational Model (Gavilán 2006, 2017), and takes into account the Diversity of Disability Model and the current perspectives about the visual impairment. In this work we’ll present some of the results got through 22 visually impaired participants by means of two modalities of the theoretical model adopted: the Specific Individual Process and the Micro-process. Three key findings have been reached. At first place, we’ve found the influence of the subjective perspective of people themselves in front of their visual impairment as a prevailing factor in their choices, emphasized or moderate, according their family perspective. In second place, the similarity of the source factors of educational/occupational choices among sighted and visually impaired people, but influenced by their disability condition. Finally, we’ve found the deficiency/unsuitability of the guidance processes.